Analisis Kekeringan Untuk Mitigasi Kebakaran Lahan Gambut Menggunakan Data Satelit Berbasis Sistem Informasi Geografis - Hilda Febrina; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Drought is a problem that occurs in every year whose timing can not be known certainty. Therefore, it is necessary to do drought index analysis to determine the level of drought in order to become early warning of drought. There are several methods that can be done to determine the level of drought of a region, one of them is the SPI (Standardized Precipitation Index) method. The SPI method is a suitable method used to calculate meteorological drought. The SPI method uses rainfall data as its input data. TRMM rainfall data is satellite rainfall data that can be used for calculation of SPI value. The research location is Bukit Batu District, Bengkalis Regency, Riau Province which has been divided into 23 grid with 0.10 x 0.10 grid width. From the results of SPI calculations displayed in the form of graphs can be concluded that each grid has the same trendline. The SPI values that have been obtained are then correlated with the number of hotspots. From 23 grid of Bukit Batu Subdistrict, BB7 grid is the grid with the highest number of hotspots in 2014.Keyword: Drought Index, SPI, TRMM, Hotspot